2012
DOI: 10.1007/s00402-012-1580-x
|View full text |Cite
|
Sign up to set email alerts
|

Precision of novel radiological methods in relation to resurfacing humeral head implants: assessment by radiostereometric analysis, DXA, and geometrical analysis

Abstract: Radiostereometric analysis and DXA can be used for evaluation of RHHI, but expectedly with a lower precision as compared to standards of TKA or THA. Geometric analysis of the prosthetic shoulder is precise. We interpret that the early radiological and clinical results of the two RHHI are comparable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
2
16
1
Order By: Relevance
“…Furthermore, the osseous integration into the implant surface and coating seems to work for all evaluated CRSA implants. Accordingly, Stilling et al, did not find a difference in a radiostereometric migration analysis after 6 month for the Copeland and Global C.U.P . However, it has to be noted that the limited number of retrievals, the different CRSA designs and the varying patient characteristics probably do not provide enough statistical power to detect a differences between the implant geometries.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the osseous integration into the implant surface and coating seems to work for all evaluated CRSA implants. Accordingly, Stilling et al, did not find a difference in a radiostereometric migration analysis after 6 month for the Copeland and Global C.U.P . However, it has to be noted that the limited number of retrievals, the different CRSA designs and the varying patient characteristics probably do not provide enough statistical power to detect a differences between the implant geometries.…”
Section: Discussionmentioning
confidence: 95%
“…Studies on the humeral head resurfacing prosthesis showed especially poor precision values (Stilling et al. 2012, Mechlenburg et al. 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the preliminary results in a randomised clinical trial comparing the Copeland hemiarthroplasty with the Global CAP hemiarthroplasty. 26 The definition of a young patient is disputed, and limits of 50 or 55 years have been suggested. 3,6,27,28 We decided to use the limit of 55 years as this was used in two previous studies of resurfacing hemiarthroplasty in young patients.…”
Section: Discussionmentioning
confidence: 99%